If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = (x + 1)(x + y) Reorder the terms: x = (1 + x)(x + y) Multiply (1 + x) * (x + y) x = (1(x + y) + x(x + y)) x = ((x * 1 + y * 1) + x(x + y)) x = ((1x + 1y) + x(x + y)) x = (1x + 1y + (x * x + y * x)) Reorder the terms: x = (1x + 1y + (xy + x2)) x = (1x + 1y + (xy + x2)) Reorder the terms: x = (1x + xy + x2 + 1y) x = (1x + xy + x2 + 1y) Solving x = 1x + xy + x2 + 1y Solving for variable 'x'. Combine like terms: x + -1x = 0 0 + -1xy + -1x2 + -1y = 1x + xy + x2 + 1y + -1x + -1xy + -1x2 + -1y -1xy + -1x2 + -1y = 1x + xy + x2 + 1y + -1x + -1xy + -1x2 + -1y Reorder the terms: -1xy + -1x2 + -1y = 1x + -1x + xy + -1xy + x2 + -1x2 + 1y + -1y Combine like terms: 1x + -1x = 0 -1xy + -1x2 + -1y = 0 + xy + -1xy + x2 + -1x2 + 1y + -1y -1xy + -1x2 + -1y = xy + -1xy + x2 + -1x2 + 1y + -1y Combine like terms: xy + -1xy = 0 -1xy + -1x2 + -1y = 0 + x2 + -1x2 + 1y + -1y -1xy + -1x2 + -1y = x2 + -1x2 + 1y + -1y Combine like terms: x2 + -1x2 = 0 -1xy + -1x2 + -1y = 0 + 1y + -1y -1xy + -1x2 + -1y = 1y + -1y Combine like terms: 1y + -1y = 0 -1xy + -1x2 + -1y = 0 Factor out the Greatest Common Factor (GCF), '-1'. -1(xy + x2 + y) = 0 Ignore the factor -1.Subproblem 1
Set the factor '(xy + x2 + y)' equal to zero and attempt to solve: Simplifying xy + x2 + y = 0 Solving xy + x2 + y = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 5=0.6w | | 7x+38=-5x-10 | | W+233=319 | | -1.5d=8 | | D-67=23 | | 840=45+f | | y^2-5= | | 314+z=350 | | 0.6x=-4 | | 0.7y=12 | | 12z-12-4z=6-2z+32 | | (x^2-1)(x^2+2x+1)= | | 3x^5y^3+81x^5= | | 5y^2-5= | | -3x^2(4x^2-3x+3)= | | y^2-4y-5= | | y-8=15 | | -(6y-5)-(-5+4)=3 | | 14-x=8 | | x^2+20x-69=0 | | M^2+7m-8= | | y=6x+32 | | 3x-8=34 | | 2x/3=x/7-11 | | H=-5t^2+32t-12 | | 9x-1+3x=6x-60 | | 10/158/25= | | 2-6x=3x-4 | | 3w+1=3w+8 | | 3x+1-4=4 | | (3x^2-x)(3x-x^2)= | | 33=[a+12] |